Peat - Topcuoğlu, Bülent; Turan, Metin (IntechOpen, 2018)
Peatlands are formed in limited areas and have significant effects on our planet. As a result of their use peatlands are continually shrinking on a daily basis. This edited book, Peat, is intended to provide an overview of different perspectives of peat material in relevant disciplines. We hope that this book will contribute to the expectations and needs of all relevant disciplines that share their findings for future research.